Interaksi sosial dan politik dalam dinamika lahirnya Pancasila - ria, Mochamad zaka (Maliki Interdisciplinary Journal, 2025)
This journal discusses the important role of social interaction and political dynamics in the birth of Pancasila as the foundation of the Indonesian state during the independence period in 1945. This study uses a qualitative approach with historical analysis of secondary sources, including historical documents and social and political theories. The findings show that social interaction, especially the active role of youth and local cultural values ​​such as mutual cooperation, contributed significantly to building national awareness and unity. Meanwhile, political dynamics, through the process of negotiation and compromise in the BPUPKI and PPKI sessions, succeeded in uniting various diverse ideologies into a value consensus that was then formulated in Pancasila. The results of the study confirm that Pancasila is not only an ideological symbol, but also an inclusive, pragmatic guideline, relevant to facing current socio-political challenges such as extremism and division. Recommendations related to education and public policy are also presented to maintain and strengthen the values ​​of Pancasila in the modern era.